THE CONTENT AND ESSENCE OF THE CONCEPTS OF MOTIVATIONAL APPROACH” AND “CREATIVE THINKING (Eureka Journal of Education & Learning Technologies, 2026)
This article presents the content and essence of the concepts of “motivational approach” and “creative thinking” and their coverage in various scientific sources. It also presents considerations on the study of the process of developing creative thinking skills of students of pedagogical education based on the Motivational Approach.
Keywords: Motivational approach, motive, motivation, creativity, creative thinking, pedagogical higher education institution, development of creative qualities, specialist.